Does bottle color protect red wine from photo‐oxidation?. Issue 5 (22nd March 2019) - Guerrini, Lorenzo; Pantani, Ottorino‐Luca; Politi, Styliani; Angeloni, Giulia; Masella, Piernicola; Calamai, Luca; Parenti, Alessandro
Abstract : Even if bottled red wines have an extended shelf life, they undergo several chemical changes, and producers are well aware of the importance of the packaging. However, there is a lack of research into the effect of light on their composition. Therefore, the storage conditions of a Sangiovese wines with respect to artificial light exposure (present/absent) and bottle color (transparent, brown, and green) were investigated. Thirty‐five chemical characteristics (physicochemical, UV‐VIS indexes, and volatile compounds) were recorded after 6 months of storage. Light exposure caused significant differences in total SO2 and a shift from red to yellow/orange color. For wines kept in transparent bottles, total red pigments, total phenol index, monomeric anthocyanins, copigmentation, chemical age, and some volatile compounds showed significant differences, depending on whether it was exposed to light or not. On the contrary, light exposure was found not significant for the wine stored in green and brown bottles, Finally, an overall increase in variability was found for light‐exposed wine in transparent bottles which could be considered, in itself, a measure of lack of quality. Abstract : A Sangiovese wine was stored in bottles of different colour with and without light. Brown and green bottles protect wine from oxidation better than transparent bottles. Bottles exposed to light, particularly transparent, had higher variability, which could be considered a measure of lack of quality.